Construction Method and Process Optimization of Prestress Reverse Tensioning for Large-Span Bidirectional Suspension Steel Roof Structures - Wang Yao; Zhang Hao; Zhang Feng; Li Yang; Li Dong; Bao Min (Advances in Civil Engineering)
For medium and small-scale steel structure stadiums, in order to minimize the impact of the construction process on the structural state, a prestressing construction process tailored to medium and small stadiums is proposed, taking full advantage of the inherent elastic deformation range of steel structures. The main steps of the process involve the construction of the main truss first. After the main truss construction is completed, it is lowered to a certain position within its elastic range using cables. The roof grid is then connected to the main truss. Once all connections are completed, the cable tension is gradually released. After the cable tension is released, the main truss exhibits a certain degree of rebound. During the rebound process, the roof grid forms a prestressed structure, ensuring stability and integrity between the main truss and the roof. Through numerical simulation, process analysis is conducted on this construction process, and the optimal construction scheme is proposed.